Carotid endarterectomy using regional anesthesia: technique and considerations - Padmanaban, Varun; Caldwell, Catherine; Milne, Indigo; Hazard, Sprague W.; Harbaugh, Robert E.; Church, Ephraim W. (Frontiers in Surgery, 2024)
BACKGROUND: Carotid endarterectomy (CEA) is one of the most effective operations in minimizing stroke risk in both symptomatic and asymptomatic patients with carotid stenosis in the United States. Awake CEA with regional anesthesia may decrease both perioperative complications and length of hospital stay. Techniques of performing awake CEA is not often described in published literature. OBJECTIVE: To describe our experience with CEA using regional anesthesia with a focus on patient selection, anatomic variations, and surgical technique including cervical regional block.We particularly focus on nuances of the awake approach. METHODS: CEA using regional anesthesia is described in detail.RESULTS: Successful use of regional anesthesia during CEA without complication. CONCLUSION: Regional anesthesia for CEA is an advantageous approach for cervical plaque removal in appropriate patients. Thoughtful patient selection, as well as understanding of anatomy and its variants, is required. Potential advantages and disadvantages are discussed.RUNNING TITLE: Awake CEA: techniques and consideration. KEY WORDS: Awake carotid endarterectomy, regional anesthesia, cervical block. ABBREVIATIONS: CEA (carotid endarterectomy), ICA (internal carotid artery), CCA (common carotid artery), ECA (external carotid artery),